ON THE DEVELOPMENT OF ADIPOSE EYELIDS IN THE FRY OF LIZA MACROLEPIS AND L. PARSIA - Rengaswamy, C P (Indian Journal of Fisheries, 2011)
The adipose eyelid, a fatty tissue deposition on the eye which at times may intrude over the orbit, is one of the important taxonomic characters used by several workers for distinguishing the different genera and sepcies of mullets. But there is considerable confusion regarding the formation of adipose eyelids in mullets. Liza was proposed as a subgenus to include those without an adipose eyelid. As there are all stages of obsolescence of eyelids, this character was never satisfactory though the name was used generically and sub-generically by several workers.